Characterizations of Resilience in Poststroke Aphasia: A Scoping Review and Considerations for Treatment and Research. Issue 3 (July 2022) - Hunting Pompon, Rebecca; Mach, Helen
Abstract : The definitions and features of resilience, the process and outcome of successfully responding to adversity, are variable across the disability and rehabilitation literatures, and its influence on aphasia treatment and outcomes is as of yet unknown. This scoping review identified and thematically categorized characterizations and descriptions of resilience and the similarly used terms adaptation, adjustment, and coping in the aphasia research literature. Frequently noted features of resilience included internal/cognitive emotional responses, such as positive self-concept, attitude/outlook, and psychological function, as well as external/behavioral responses, such as engaging in new activities and opportunities for social connection. These general features align with a definition of resilience recently developed for individuals with chronic impairment. And, although little information about the influence of resilience on treatment engagement and outcomes emerged from the reviewed literature, a number of clinical considerations and research directions are suggested.